Pengintegrasian Elemen Gamifikasi pada Situs Google untuk Meningkatkan Kemampuan Berpikir Kritis Siswa SMKN 2 Situbondo - Komariyatul. H, Siti Nur; Surur, Miftahus; Razaki, Rahmat Shofan; Suparto, Arico Ayani (STKIP PGRI SITUBONDO, 2024)
Abstract: This study uses the type of Research and Development (R&D) research with the ASSURE model, which consists of the Analyze, State, Select, Utilize, Require, Evaluate procedures. The media developed has gone through three tests, namely validity test, practicality test, and effectiveness test. The instruments used in this study were validation questionnaires, student response questionnaires, and tests. The study was conducted at SMKN 2 Situbondo involving one class with 27 students. The results of the study showed that the Google Sites web learning media met the validity test from media experts with a value of 92.7% (very valid) by information technology media expert lecturers and 98.8% (very valid) by accounting teachers. In addition, the Google Sites web learning media also improved students' critical thinking skills as evidenced by the sig. (2-tailed) value of 0.000 which indicates that there is a difference or influence of the use of the media because the magnitude of the test results <the significance level value set, which is 0.05. The use of Google web learning media also received a positive response from students, as indicated by the average number of assessments for each point of the student response questionnaire of 98.4%.